Pengembangan Panduan Pencegahan Ulkus Dekubitus di Ruangan Intensive Care Unit (ICU) - Anita Yustina; Setiawan Setiawan; Imam Budi Putra (Journal of Telenursing (JOTING), 2021)
This study aims to develop guidelines for decubitus ulcers in the ICU at USU Hospital. This type of research is action research in 1 cycle. The instrument used was a Focus Group Discussion (FGD) guide and a nurse's knowledge questionnaire about decubitus ulcers. Participants in this study were 15 nurses who were selected by purposive sampling. The results showed that the percentage value before the formulation of guidelines for the prevention of decubitus ulcers was 66.67% which stated that the level of knowledge was good and 33.33%, which noted that the level of knowledge was sufficient and the level of expertise lacked as much as 0%. After the formulation of the guidelines, the results were 93.4%, where the nurses' level of knowledge was declared good. The level of expertise of nurses that was reported sufficient was 6.6% and the level of expertise of nurses that was insufficient was 0%. In conclusion, with the implementation of decubitus ulcers guidelines, ICU nurses' knowledge of decubitus ulcers prevention has increased. The components of the decubitus ulcers guide consist of the concept of a decubitus ulcers, scope and Standard Operating Procedure (SOP). Keywords: Intensive Care Unit (ICU), Decubitus Ulcer Guide, Nurse